Impact of the Ruble exchange rate regime and Russia's war in Ukraine on wheat prices in Russia - Stanislav Yugay; Linde Götz; Miranda Svanidze (Agricultural Economics, 2024)
We assess exchange rate pass-through when the Ruble exchange rate was managed in comparison with when it became free-floating. Estimates of the error correction model for milling wheat prices suggest exchange rate pass-through to be strongest in Russia's North Caucasus, the region closest to the Black Sea ports, and weakest in the remote regions of Volga and West Siberia since the Ruble exchange rate became free-floating in 2014. In contrast, we find Russian regional wheat prices and the Ruble/USD exchange rate not cointegrated when the exchange rate was managed. Further, feed wheat (Class 5) is only weakly integrated compared to wheat Classes 3 and 4 for human consumption. With Russia's invasion of Ukraine, exchange rate pass-through to Russian wheat prices has decreased sharply. Thus, the Ukraine war drives the disintegration of Russia's wheat sector from international markets and adds to the risks of supply chain disruption and geopolitical risks, which may increase export supply volatility. To strengthen trade resilience, countries that are dependent on wheat imports should diversify their import sources.
Keywords: Q02; Q13; Q17; 330; exchange rate pass-through; food security; Russia; the war in Ukraine; wheat prices